Organizational communication approaches and processes - Miller, Katherine 1959- (Cengage Learning/Wadsworth, 2015)
Machine generated contents note: ch. 1 The Challenge of Organizational Communication -- Our Complicated World -- Globalization -- Terrorism -- Case in Point: Can Tragedy Lead to Change? -- Climate Change -- Changing Demographics -- Case in Point: 400 Million People -- Complicating Our Thinking about Organizations -- Complicating Our Thinking about Communication -- Looking Ahead -- ch. 2 Classical Approaches -- The Machine Metaphor -- Henri Fayol's Theory of Classical Management -- Elements of Management -- Principles of Management -- Principles of Organizational Structure -- Principles of Organizational Power -- Principles of Organizational Reward -- Principles of Organizational Attitude -- Summary of Fayol's Theory -- Case in Point: Are There Limits to Rewards? -- Max Weber's Theory of Bureaucracy -- Frederick Taylor's Theory of Scientific Management -- Impetus for the Theory of Scientific Management -- Components of Scientific Management -- Case in Point: Systematic Surgery